Altered spontaneous neural activity in the occipital face area reflects behavioral deficits in developmental prosopagnosia. (August 2016) - Zhao, Yuanfang; Li, Jingguang; Liu, Xiqin; Song, Yiying; Wang, Ruosi; Yang, Zetian; Liu, Jia
Abstract: Individuals with developmental prosopagnosia (DP) exhibit severe difficulties in recognizing faces and to a lesser extent, also exhibit difficulties in recognizing non-face objects. We used fMRI to investigate whether these behavioral deficits could be accounted for by altered spontaneous neural activity. Two aspects of spontaneous neural activity were measured: the intensity of neural activity in a voxel indexed by the fractional amplitude of spontaneous low-frequency fluctuations (fALFF), and the connectivity of a voxel to neighboring voxels indexed by regional homogeneity (ReHo). Compared with normal adults, both the fALFF and ReHo values within the right occipital face area (rOFA) were significantly reduced in DP subjects. Follow-up studies on the normal adults revealed that these two measures indicated further functional division of labor within the rOFA. The fALFF in the rOFA was positively correlated with behavioral performance in recognition of non-face objects, whereas ReHo in the rOFA was positively correlated with processing of faces. When considered together, the altered fALFF and ReHo within the same region (rOFA) may account for the comorbid deficits in both face and object recognition in DPs, whereas the functional division of labor in these two measures helps to explain the relative independency of deficits in face recognition and object recognition in DP. Highlights: Developmental prosopagnosia (DP) also showed deficits in object recognition. Reduced resting-state activity was observed in the right occipital face area (rOFA). rOFA's fluctuation magnitude (fALFF) was related to general object recognition. rOFA's local connectivity (ReHo) was related to face-specific recognition.